Factors Influencing Effectiveness of Celebrity Endorsement in Advertising - Akram, Saima; Nazam, Muhammad; Mubeen and Sana Rabbi Ch, Riaqa (British Journal of Marketing Studies, 2016)
Celebrity endorsement is a widely used tactic in marketing and a useful way of pushing a product in crowded markets, much research has been done on the selection and effect of celebrity endorsement. This study identifies key factors that determine the effectiveness of the celebrity endorsements in advertisements. The study adopts a quantitative approach, with a structured questionnaire as the main tool. A survey of 245 samples was conducted and results indicated that all the observed factors influences greatly on the effectiveness of the celebrity endorsements except one and that is attractiveness. These factors are popularity, knowledge and skills, credibility, celebrity-brand match up and loyalty of the celebrity. Also, this study found out that the price is the major consideration in consumer buying decisions. Marketers should devise the advertising strategies that address all the observed factors. The study concludes with the agenda for future research.